Quality control guidelines for testing cefotetan in the reference agar dilution procedure for susceptibility testing of anaerobic bacteria. - Zabransky, R J (1989)
Reference values for quality control of in vitro susceptibility tests with cefotetan against anaerobic bacteria were determined in two independent multilaboratory studies with the approved National Committee for Clinical Laboratory Standards agar dilution method and three control strains (Bacteroides fragilis ATCC 25285, Bacteroides thetaiotaomicron ATCC 29741, and Clostridium perfringens ATCC 13124). The results of the two studies were in agreement. The recommended MIC control limits for B. fragilis ATCC 25285 and B. thetaiotaomicron ATCC 29741 are 4.0 to 16 micrograms/ml and 32 to 128 micrograms/ml, respectively. MICs for C. perfringens ATCC 13124 were too variable to be useful for controlling tests with cefotetan.